LEGAL ANALYSIS OF LEGAL PROTECTION FOR WORKERS IN THE AREA OF OCCUPATIONAL SAFETY AND HEALTH (OSH) IN THE INDUSTRIAL SECTOR (RESEARCH STUDY IN THE INDUSTRIAL AREA OF BATAM CITY) - Erniyanti; Muh. Aliuddin Arief; M. Soerya Respationo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Occupational Safety and Health (OSH) is a fundamental right of every worker that must be guaranteed through an adequate legal protection system. In the midst of the development of industrial area of Batam City as a national strategic area, the complexity of work relationship and high level of work risk become a challenge in the implementation of OHS protection. This research is motivated by the in-creasing number of work accidents in the industrial area of Batam City, which shows a gap between legal arrangements and implementation of labor protection.The purpose of this study is to analyze the ap-plicable legal arrangements related to OHS protection, assess the implementation of legal protection of workers in the field, and identify obstacles and strategic efforts that need to be made in the context of legal protection.The methods used in this research are normative juridical and empirical juridical ap-proaches, with data collection techniques through literature studies and interviews with relevant parties, including the Kepri Provincial Manpower Office, industrial companies, K3 training institutions, and K3 practitioners. The analysis was conducted by referring to the statute approach and socio-legal ap-proach, based on John Rawls' theory of justice, Lawrence M. Friedman's legal system theory, and Sudikno Mertokusumo's theory of legal certainty.The result shows that although the normative regu-lation on OSH protection is quite complete, its implementation in Batam City still faces various ob-stacles, such as lack of supervision, low legal awareness, and weak deterrent effect from legal sanctions. Comprehensive reform of OSH regulation, capacity building of labor inspectors, and synergy between government, employers, and workers in building OSH conscious culture are needed.